Kata Yahudi dalam Al-Qur’an: Analisis Semantik - Nur Anisa Septiani (UIN Sunan Gunung Djati Bandung, 2022)
This paper is a form of research curiosity about how the Qur'an discusses the word Judaism with semantic analysis. Which, when viewed today, is a cruel Jew, an occupier, terrorizing Palestinians. So that researchers feel the need to find out. Does God describe the Jews according to what is happening today or not. The formal object of this research is the semantic theory, while the material object is the word Judaism in the Qur'an. By using a qualitative method, this paper produces a classification in which many different meanings and contexts are expressed in the derivation of Jewish words, Jewish characters or attitudes both to Allah and to Muslims.